Psychosocial function, legal involvement and violence in mental disorder. Issue 1 (3rd December 2021) - Buchanan, Alec; Moore, Kelly E.; Pittman, Brian; McKee, Sherry A.
Abstract: Background: The correlates of legally significant outcomes that have been identified in people with mental disorders are of limited value in understanding the mechanisms by which these outcomes occur. Aims: To describe the relationships between mental disorder, impaired psychosocial function, and three legally significant outcomes in a representative sample of the US population. Methods: We used a population survey, the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC-III, sample size 36, 309), to identify people who self-reported serious trouble with the police or the law over the past 12 months and two lifetime outcomes, being incarcerated and engaging in violence to others. DSM-5 categories were generated using the Alcohol Use Disorder and Associated Disabilities Interview Schedule-5. Psychosocial function was assessed using social and role-emotional function scores of the 12-Item Short-Form Health Survey Version 2. Results: Participants with mental disorder, but not people with no diagnosis, who reported serious trouble with the police or with the law during the previous 12 months reported significantly worse psychosocial function than those who did not report such trouble. The size of the statistical effect varied by diagnosis, moderate for some forms of mental illness and for alcohol abuse and nonsignificant for drug abuse and the personality disorders. Effect sizes were largest for diagnoses where legally significant outcomes were least common. Conclusions: The effect of impaired psychosocial function, for instance in disrupting family and social networks that would otherwise protect against these legally significant outcomes, warrants further investigation in studies with longitudinal designs.